1997
DOI: 10.1161/01.cir.96.10.3626
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Concentrations of Estradiol Attenuate Endothelin 1–Induced Coronary Vasoconstriction In Vivo

Abstract: We conclude that estradiol attenuates ET-1-induced vasoconstriction, possibly through effects on the ET(A) receptor, because selective ET(B) receptor-induced stimulation with sarafotoxin remained unchanged. Such an effect on the ET(A) receptor may relate to the antianginal properties of estrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
3
41
2
1
Order By: Relevance
“…We found that the ET-1-induced constrictive response is unaffected by short-term exposure to physiological (1 × 10 −9 M to 1 × 10 −8 M) and pharmacological (1 × 10 −7 M to 1 × 10 −4 M) concentrations of 17β-estradiol in fresh and organ cultured coronary arteries. This contrasts previous studies which demonstrated physiological concentrations of 17β-estradiol reduced the constrictive response to ET-1 in market-age pigs (Sudhir et al, 1997;Teoh et al, 1999). However, Wynne et al (2004) similarly found that advanced age decreases the inhibitory effect of 17β-estradiol on calcium influx.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We found that the ET-1-induced constrictive response is unaffected by short-term exposure to physiological (1 × 10 −9 M to 1 × 10 −8 M) and pharmacological (1 × 10 −7 M to 1 × 10 −4 M) concentrations of 17β-estradiol in fresh and organ cultured coronary arteries. This contrasts previous studies which demonstrated physiological concentrations of 17β-estradiol reduced the constrictive response to ET-1 in market-age pigs (Sudhir et al, 1997;Teoh et al, 1999). However, Wynne et al (2004) similarly found that advanced age decreases the inhibitory effect of 17β-estradiol on calcium influx.…”
Section: Discussioncontrasting
confidence: 98%
“…As similarly demonstrated by others using market-age pigs (6 to 12 months) (Barber et al, 1996;Sudhir et al, 1997;Teoh et al, 2000), our study shows that 17β-estradiol can induce the relaxation of a pre-constricted artery. However, the transition of arterial cells to a proliferative phenotype with organ culture (Hill et al, 2001;Hill et al, 2000), attenuated the 17β-estradiol-induced arterial relaxation.…”
Section: Discussionsupporting
confidence: 89%
“…1-2 Because ET-1 plays a role in the pathogenesis of DOCA-salt hypertension, [13][14][15][16][17] it is possible that the attenuated development of hypertension in female DOCA-salt rats may be related to a modulation exerted by the gonadal hormones on ET-1 effects on the cardiovascular system. [5][6][7][8][9][10][11] We have recently reported that in DOCA-salt hypertension, male rats display altered vascular and pressor responses to ET-1 and to the ET B agonist IRL-1620 and that these alterations are attenuated in female rats. 3,4 We specu- lated that the differential and gender-related alterations in ET-1-mediated effects in DOCA-salt hypertension may be important in the higher blood pressure levels observed in male DOCA-salt hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our own work using a rat model of menopause (12-mo-old ovariectomized Sprague-Dawley rats) found increased mesenteric artery reactivity to big ET-1 (an ET-1 precursor) compared with young cycling females, which was ameliorated in the "menopausal" animals receiving chronic estrogen treatment (55). A study by Sudhir et al (93) showed an attenuation of ET-1 responses in coronary arteries following acute intracoronary injection of a physiologically relevant dose of estrogen, suggesting the possibility of rapid nongenomic estrogen effect. These in vivo findings clearly show a key role for estrogen in protecting the cardiovascular system from ET-1-mediated pathological change, which may be lost during menopause.…”
Section: Sex Hormones and Endothelinmentioning
confidence: 97%